2020
DOI: 10.15835/nbha48412104
|View full text |Cite
|
Sign up to set email alerts
|

Determination of allelopathic properties of Acacia catechu (L.f.) Willd.

Abstract: Plants possessing allelopathic potential could be used as a source of bio-herbicide to help decrease the use of synthetic herbicides. Acacia catechu (L.f.) Willd., a deciduous tree from the Mimosaceae family, has been reported to have medicinal properties. However, there have been no reports on the allelopathy of this tree. Therefore, the leaf extracts of A. catechu were examined for allelopathic potential using six concentrations: 0.001, 0.003, 0.01, 0.03, 0.1, and 0.3 g dry weight equivalent extract mL-1. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The I 50 values from Table 1 also indicate species-specific phytotoxicity of the extracts. This type of allelopathic activity of plant extracts has been reported by many researchers [39][40][41][42]. Our preceding studies with Albizia richardiana also show these types of dose-dependent and species-specific inhibitory activity against various tested plants [ [43][44][45].…”
Section: Discussionsupporting
confidence: 68%
“…The I 50 values from Table 1 also indicate species-specific phytotoxicity of the extracts. This type of allelopathic activity of plant extracts has been reported by many researchers [39][40][41][42]. Our preceding studies with Albizia richardiana also show these types of dose-dependent and species-specific inhibitory activity against various tested plants [ [43][44][45].…”
Section: Discussionsupporting
confidence: 68%
“…Aqueous methanolic extracts of Albizia richardiana leaves significantly limited the growth (shoot and root) of the tested plant species, and the level of suppression increased with increasing extract concentration. Other studies have also reported the same types of concentrationdependent suppression using extracts of various plant species [44][45][46][47]. The I 50 values of the Albizia richardiana leaf extracts indicated that growth suppression was tested species dependent (Table 1).…”
Section: Discussionmentioning
confidence: 63%
“…Allelopathic substances can influence physiological activities and factors such as seed germination, photosynthesis, respiration, transpiration, ion uptake, water status, stomatal opening, enzyme activity, and the hormone levels of plants [44]. These phytotoxic substances also influence cell division and differentiation, gene expression, signal transduction, cell wall structure, cell membranes, and cell permeability [45,46].…”
Section: Discussionmentioning
confidence: 99%